Island girls [large type] : a novel - Thayer, Nancy, 1943- (Center Point Large Print, 2013)
Charming ladies' man Rory Randall dies with one last trick up his sleeve: his will includes a clause mandating that his daughters, all from different marriages, must spend a summer at his posh Nantucket house. At least, they must comply if they hope to inherit it. The three sisters are not on good terms, but they do show up, with surprising and dramatic consequences.